The ecology of peace : preparing Colombia for new political and planetary climates (2018)
ABSTRACT: Colombia, one of the world’s most species-rich nations, is currently undergoing a profound social transition: the end of a decadeslong conflict with the Revolutionary Armed Forces of Colombia, known as FARC. The peace agreement process will likely transform the country’s physical and socioeconomic landscapes at a time when humans are altering Earth’s atmosphere and climate in unprecedented ways. We discuss ways in which these transformative events will act in combination to shape the ecological and environmental future of Colombia. We also highlight the risks of creating perverse development incentives in these critical times, along with the potential benefits – for the country and the world – if Colombia can navigate through the peace process in a way that protects its own environment and ecosystems.